Survey of Land and Real Estate Transactions in the Russian Federation : Statistical Analysis of Selected Hypotheses - Kisunko, Gregory; Coolidge, Jacqueline (World Bank, Washington, DC, 2012)
This paper analyzes land transactions between municipalities and private businesses based on official data and business surveys in 15 regions of the Russian Federation. Since the Russian Federation passed the new Land Code in 2001, land privatization has been officially encouraged by the federal government and in particular, land under previously privatized buildings was supposed to be privatized to the owner at a nominal price. The paper shows that many subnational authorities (which own or control the vast majority of land of interest to businesses) appear to use a combination of high statutory land buy-out prices and administrative barriers to deter land privatization and to offer "long-term leases" (which are not fully marketable) instead. On the other hand, regions that have established low buy-out prices and taken steps to remove unnecessary administrative barriers to land privatization appear to have higher rates of land ownership by businesses, and to face lower levels of corruption in the privatization process. The paper concludes that further reductions in the statutory prices for privatization of land under buildings and elimination of unnecessary administrative barriers should help to encourage further land privatization and the development of a competitive, secondary market in commercial land.